PERUBAHAN NILAI GIZI PEMPEK LENJER SELAMA PEREBUSAN - Karneta, Railia; Rejo, Amin; Priyanto, Gatot; Pambayun, Rindit (Publikasi Penelitian Terapan dan Kebijakan, 2013)
Pempek lenjer cooking is done by boiling, which aims to make tapioca flour (starch) undergo gelatinization process, so the starch granules swell and denatured proteins. Long and high temperature on the boiling process pempek be controlled because it affects the nutritional value of pempek. The purpose of this study is to see the effect of the formula and the temperature at the center point to changes in the nutritional value pempek lenjer during boiling. Treatment with four standard formula dough and five degree temperature treatment. The results showed that the higher the addition of starch, the water content, protein content, fat content and ash content further go down, but the levels of carbohydrates and fiber content get higher. Water content get the highest in the temperature at the center of pempek 950C, protein content, fat content, carbohydrate content, ash content, and fiber content get highest in the temperature at the center of pempek 750C.